2021
DOI: 10.1101/2021.05.03.442464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Volumetric alteration of olfactory bulb and immune-related molecular changes in olfactory epithelium in first episode psychosis patients

Abstract: BackgroundOlfactory dysfunction has been reproducibly reported in patients with psychosis, including first episode psychosis (FEP) patients. Consistently, structural abnormalities in the olfactory bulb (OB), a key region of the peripheral olfactory system, have also been reported in psychotic disorders. Meanwhile, air pollution and viral infections in the upper respiratory tract, including those of SARS-CoV-2, are reportedly risk factors for brain dysfunction and mental disorders. These risk factors can distur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Several groups have established similar but slightly different protocols for preparing ONCs, but all these cells are cultured in vitro and can be stored until further use. These cells share molecular signatures relevant to neurons (Fan et al, 2013;Kano et al, 2013;English et al, 2015;Feron et al, 2016;Lavoie et al, 2017;Rhie et al, 2018;Sumitomo et al, 2018;Doostparast Torshizi et al, 2019;Evgrafov et al, 2020;Takayanagi et al, 2021;Tee and Mackay-Sim, 2021;Yang et al, 2021). There are advantages of using ONCs to fill the gap in the "druggable genome" approach: first, we can conduct symptomatic and cognitive assessment in parallel to nasal biopsy and molecular analysis of ONCs from the same subjects; second, at least by our own protocol, ONCs can be used for biochemical and pharmacological studies because of their homogeneity shown at the histochemical levels (Kano et al, 2013;Takayanagi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have established similar but slightly different protocols for preparing ONCs, but all these cells are cultured in vitro and can be stored until further use. These cells share molecular signatures relevant to neurons (Fan et al, 2013;Kano et al, 2013;English et al, 2015;Feron et al, 2016;Lavoie et al, 2017;Rhie et al, 2018;Sumitomo et al, 2018;Doostparast Torshizi et al, 2019;Evgrafov et al, 2020;Takayanagi et al, 2021;Tee and Mackay-Sim, 2021;Yang et al, 2021). There are advantages of using ONCs to fill the gap in the "druggable genome" approach: first, we can conduct symptomatic and cognitive assessment in parallel to nasal biopsy and molecular analysis of ONCs from the same subjects; second, at least by our own protocol, ONCs can be used for biochemical and pharmacological studies because of their homogeneity shown at the histochemical levels (Kano et al, 2013;Takayanagi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%